Development of a Sound Wave E-module to Enhance Grade XI Students’ Critical Thinking Skills: An ADDIE-Based Development Study at SMAN 1 Padarincang - Maelani, Maya; Haryadi, Rudi; Septiyanto, Rahmat Firman (SEARCH: Science Education Research Journal, 2026)
The development of technology in the digital era requires education to design learning resources that support 21st-century skills, including critical thinking. Critical thinking is important in physics learning because students must interpret phenomena, analyze relationships among variables, evaluate evidence, and draw scientific conclusions rather than merely memorize formulas. Sound wave material is often considered difficult by students because several concepts are abstract and are not sufficiently supported by interactive teaching materials. This study aimed to develop a sound wave e-module, determine its feasibility, examine student responses, and identify its potential to improve the critical thinking skills of Grade XI students at SMAN 1 Padarincang. This research used a Research and Development (R&D) approach with the ADDIE model, limited to four stages: Analysis, Design, Development, and Implementation. The results showed that the e-module achieved a very feasible category based on media expert validation, with percentages of 98%, and material expert validation, with percentages of 93,33%. Student responses were in the very good category, with an average percentage of 86.98%. The mean score increased from 19.31 in the pretest to 26.00 in the posttest, with an N-gain of 0.32, which is categorized as moderate. These findings indicate that the developed sound wave e-module is feasible, practical, and has the potential to support students’ critical thinking skills in physics learning.